DIVISOR: Real-time Drilling Visualizations for Virtual Reality - Porcino, Thiago; Dórea, Márcia; Barboza, Diego; Oliveira, Wesley; Romani, Eric; Perin, Fernando; Batista, João (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Well drilling is one of the most expensive tasks in oilfield exploration and development projects, especially in offshore assets. Thus, this activity is under constant evolution, given that any improvement in equipment or process can result in significant savings for the company operating that field. Meanwhile, virtual reality (VR) is one of the vital industry 4.0 trends to enable simulations and training safely for users. This work aims to provide a new tool to increase the drilling team’s efficiency by recreating drilling visualizations in a virtual environment. This environment enables training, evaluating, and simulating different scenarios in a well drilling and provide realtime insights to the engineers when coupled with other diagnostics tools.